2014
DOI: 10.1002/2014jb011253
|View full text |Cite
|
Sign up to set email alerts
|

Mantle transition zone discontinuities beneath the contiguous United States

Abstract: Using over 310,000 high‐quality radial receiver functions recorded by the USArray and other seismic stations in the contiguous United States, the depths of the 410 km and 660 km discontinuities (d410 and d660) are mapped in over 1,000 consecutive overlapping circles with a radius of 1°. The average mantle transition zone (MTZ) thickness for both the western and central/eastern U.S. is within 3 km from the global average of 250 km, suggesting an overall normal MTZ temperature beneath both areas. The Pacific Coa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

22
119
1

Year Published

2014
2014
2019
2019

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 105 publications
(142 citation statements)
references
References 62 publications
(100 reference statements)
22
119
1
Order By: Relevance
“…For the complete model, the median 410 and 660 depths ( d 410 and d 660 ) are 417 and 661 km, respectively, with a median transition‐zone thickness of 245 km. These values are very close to the average discontinuity depths estimated from global SS precursors (e.g., 418 and 660 km from Flanagan & Shearer, ) and the USArray receiver function analysis of Gao and Liu (), who obtained average depths across the United States of 416 and 667 km. Wang and Pavlis () obtained slightly different USArray receiver‐function average depths of 415 and 660 km; they attributed their shallower d 660 to their use of the AK135 reference 1‐D model rather than iasp91 (their application of timing corrections based on the 3‐D P wave model of Burdick et al, , may also have been a contributing factor).…”
Section: Resultssupporting
confidence: 86%
See 1 more Smart Citation
“…For the complete model, the median 410 and 660 depths ( d 410 and d 660 ) are 417 and 661 km, respectively, with a median transition‐zone thickness of 245 km. These values are very close to the average discontinuity depths estimated from global SS precursors (e.g., 418 and 660 km from Flanagan & Shearer, ) and the USArray receiver function analysis of Gao and Liu (), who obtained average depths across the United States of 416 and 667 km. Wang and Pavlis () obtained slightly different USArray receiver‐function average depths of 415 and 660 km; they attributed their shallower d 660 to their use of the AK135 reference 1‐D model rather than iasp91 (their application of timing corrections based on the 3‐D P wave model of Burdick et al, , may also have been a contributing factor).…”
Section: Resultssupporting
confidence: 86%
“…For comparison to the maps presented here, Figure S4 plots discontinuity topography results from the USArray receiver‐function study of Gao and Liu (). In general, the depth variations agree reasonably well for the 410‐ and 660‐km topography, but their transition zone thickness map shows much less variation than our results.…”
Section: Resultsmentioning
confidence: 99%
“…Nevertheless, the values in Fig. S5a and b before correction are very low compared to other studies (Chevrot et al, 1999;Gao and Liu, 2014;Tauzin and Ricard, 2014). These poor correlation values probably indicate that depth changes are not controlled primarily by temperature changes and/or that the velocity structure in the upper-mantle and the TZ are anti-correlated with anomalies of the same order but opposite sign.…”
Section: Quantitative Analysis Of Time Corrections and Discontinuity mentioning
confidence: 58%
“…Nevertheless, the mantle structure leads to large positive correlation of the observed depth values (and relative travel times), e.g., +0.94 in Chevrot et al (1999), +0.84 in Gao and Liu (2014), and +0.6 in Tauzin and Ricard (2014). Ideally, a negative or near zero correlation value is expected after correction, but in practice it is observed that velocity corrections reduce the correlation to smaller positive values (e.g., Gao and Liu, 2014;Tauzin, 2009). This residual positive correlation is partly due to the limitations of the velocity models to reproduce the real structure of the Earth, due to the assumption that depth changes are controlled only by temperature changes, and to a lesser extent due to measurement errors.…”
Section: Quantitative Analysis Of Time Corrections and Discontinuity mentioning
confidence: 99%
See 1 more Smart Citation